Three Distinct Human Behavior Symbols in Jack Stauber’s Opal (2020) - Sabila, Zeta; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (MOZAIK HUMANIORA, 2025)
This study aims to examine objects as symbols in Opal (2020). It is one of the animations that applied inanimate objects as symbols to support its theme. This animation delves into the theme of child neglect inside of a dysfunctional family and it uses cigarettes, mirrors, and pills as symbols to deliver the theme. To understand this utilization of symbols, Saussure’s semiotics theory signifier and signified is applied. By employing the semiotics theory, researchers found out that those objects are signifiers that signified ignorant, narcissistic, and abusive human behavior. Cigarettes symbolizes the  ignorant  grandfather  who is  an  active  smoker  despite  of  his health problem; mirrors symbolize the narcissistic father who is excessively obsessed with himself regardless of the harmful things he has done; pills symbolize the abusive mother who abuses her drug use just like how she abuses her daughter for her own pleasure. Therefore, this animation successfully applied objects as symbols that symbolize human behavior to support the theme of child neglect and give the impression how such harmless things can lead to bigger problems that cause harm to ourselves and others.